2016
DOI: 10.1007/s00270-016-1308-3
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Exposure of Interventional Radiologists During Computed Tomography Fluoroscopy-Guided Renal Cryoablation and Lung Radiofrequency Ablation: Direct Measurement in a Clinical Setting

Abstract: Radiation dose to interventional radiologists during renal cryoablation and lung RFA were at an acceptable level, and in line with recommended dose limits for occupational radiation exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…By manipulating the needle in real-time, subpleural and small lesions are easily approached using this technique. Although CTF may be associated with increased radiation exposure to the operator, if standard radiological prevention measures are used, CTF radiation exposure to the operator does not significantly differ from CCT [57,58].…”
Section: Ct Protocolmentioning
confidence: 97%
“…By manipulating the needle in real-time, subpleural and small lesions are easily approached using this technique. Although CTF may be associated with increased radiation exposure to the operator, if standard radiological prevention measures are used, CTF radiation exposure to the operator does not significantly differ from CCT [57,58].…”
Section: Ct Protocolmentioning
confidence: 97%
“…A radiofrequency wave causes ionic stirring and an increase in temperature in the tumor, resulting in immediate cell death by coagulation and necrosis, and delayed cell death by apoptosis [2]. The doses received by operators are within the recommended standards and do not represent a limit to the practice of RFA [3], according to recently published guidelines [4]. The first pulmonary RFA procedure was described in 2000 [5], and multiple studies have shown low rates of complications [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are reports of high radiation exposure of interventional radiologists (interventionalists), when CT fluoroscopy guidance is used [7][8][9][10] , they specifically refer to CT-guided biopsy or drainage procedures. To our knowledge, there are only two articles investigating radiation exposure of interventionalists due to CT fluoroscopy-guided PCA [11][12] . Stewart et al reported that the estimated interventionalists' radiation exposure was 0.0503 mGy/min during CT fluoroscopy-guided renal PCA [11].…”
Section: Introductionmentioning
confidence: 99%
“…Stewart et al reported that the estimated interventionalists' radiation exposure was 0.0503 mGy/min during CT fluoroscopy-guided renal PCA [11]. Matsui et al compared the direct interventionalists' radiation dose between CT fluoroscopy-guided renal PCA and lung RFA measured by electric dosimeters (for the effective dose) and thermoluminescent dosimeter rings (for the equivalent dose on the finger skin) [12]. However, there is no published study directly measuring radiation dose on multiple sites (such as the eye, hand, neck, chest and abdomen) to evaluate interventionalists' radiation exposure during CT fluoroscopy-guided PCA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation